Seismic Analysis of Tall Multistorey Structure Considering Variable Column Condition Using ETABS - Sahu, Peeyush Kumar; Chaturvedi, Prof. Anita (International Journal of Scientific Research in Civil Engineering, 2023)
One important factor that affects the project’s or building’s economy is the distance between columns. Because of this relationship between column spacing and panel size, the cost of raw materials can vary in reinforced concrete buildings. When column spacing is smaller, panels are smaller, and when column spacing is larger, panels are larger. The influence of column spacing on economy is examined in this study through a comparison of the construction of G+14 R.C. Moment Resisting Frames. Three scenarios of column spacing—C1 (300x300mm), C2 (400x400mm), and combination (C1 and C2)—are taken into consideration in order to assess the impact of column spacing on economy. Using E-TABS, the structure is modelled, examined, and designed in accordance with IS 456:2000. The amount of concrete, steel, and shuttering is calculated using the E-TABS. These models are examined to determine the relation for the ideal column dimension or combination taking into account the same building loading conditions. The building’s aspect ratio is set at 1.5, and the most cost-effective structure is determined by adding the costs of the shuttering, steel, and concrete together.